Głód słowa drukowanego. O bibliotekach i czytelnictwie w Getcie Łódzkim - Olejnik, Izabela (Acta Universitatis Lodziensis. Folia Librorum, 2013)
The article discusses the history of persecution of Jewish books after Hitler’s gained power. It also describes the fate of Jewish libraries and books in the Lodz ghetto. Apart from the pre-war J. W. Zonnenberg’s Lending Library there were also libraries established by political organizations, medical library which were used by many of the residents. The article also deals with their readers and the books they read during the years of the Holocaust.